2022
DOI: 10.7717/peerj.14211
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and cellulolytic, hemicellulolytic, and amylolytic potential of Iocasia fonsfrigidae strain SP3-1 for polysaccharide degradation

Abstract: Background Cellulolytic, hemicellulolytic, and amylolytic (CHA) enzyme-producing halophiles are understudied. The recently defined taxon Iocasia fonsfrigidae consists of one well-described anaerobic bacterial strain: NS-1T. Prior to characterization of strain NS-1T, an isolate designated Halocella sp. SP3-1 was isolated and its genome was published. Based on physiological and genetic comparisons, it was suggested that Halocella sp. SP3-1 may be another isolate of I. fronsfrigidae. Despite being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In this study, we demonstrate that a recently reported endoglucanase, designated IfCelS12A (Heng et al 2022 ), from the haloalkaliphile Iocasia fonsfrigidae strain SP3-1 (Heng et al 2019 , 2022 ) used in conjunction with a cocktail of enzymes from Clostridium thermocellum and in the presence of a mobile enzyme sequestration platform (MESP) (Mitsuzawa et al 2009 ; Ceballos et al 2014 ; Ceballos 2023 ) enhances enzymatic breakdown of multiple substrates including rice straw (RS) in IL. Our data further demonstrate that IfCelS12A has a mode of action distinct from other glycoside hydrolases within the GH12 family of enzymes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, we demonstrate that a recently reported endoglucanase, designated IfCelS12A (Heng et al 2022 ), from the haloalkaliphile Iocasia fonsfrigidae strain SP3-1 (Heng et al 2019 , 2022 ) used in conjunction with a cocktail of enzymes from Clostridium thermocellum and in the presence of a mobile enzyme sequestration platform (MESP) (Mitsuzawa et al 2009 ; Ceballos et al 2014 ; Ceballos 2023 ) enhances enzymatic breakdown of multiple substrates including rice straw (RS) in IL. Our data further demonstrate that IfCelS12A has a mode of action distinct from other glycoside hydrolases within the GH12 family of enzymes.…”
Section: Introductionsupporting
confidence: 68%
“…Discovery and characterization of cellulolytic enzymes with unique attributes, such as stability at elevated temperatures and tolerance to low pH, is an active area of research in applied microbiology (e.g., Elleuche et al 2015 ; Husain 2017 ; Thapa et al 2020 ; Dadwal et al 2021 ; Gan et al 2022 ). For this study, we characterized an endoglucanase (i.e., IfCelS12A) derived from the halophile I. fonsfrigidae strain SP3-1 isolated from a hypersaline pond in Thailand (Heng et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria of Bacillus can secrete various amylases, which can degrade starch and produce organic acids ( Ma et al, 2023 ). Moreover, it has been found that certain anaerobic bacteria within the Anaeromyxobacter genus can degrade starch into organic acids and gases, such as acetic acid, propionic acid, butyric acid, hydrogen, and carbon dioxide ( Heng et al, 2022 ). The production of these organic acids and gases was found to further promote starch degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Iocasia is a new genus of the family Halanaerobiaceae . Thus far, only one species with two strains, Iocasia fonsfrigidae strain NS-1 and strain SP3-1, has been reported [ 10 ]. Although these two strains have no confirmed toxicity, strain SP3-1 (this study) showed the highest similarity with another close-up genus in the family Halanaerobiaceae , namely, Halocella cellulosilytica DSM7362 T , at 92.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Iocasia fonsfrigidae strain SP3-1 was isolated from a salt evaporation pond as an extremely halophilic, anaerobic bacterium that grows well in a medium containing 20% ( w / v ) NaCl. The whole genome sequence of this bacterium revealed the presence of a possible DPEase gene [ 10 ] for which the amino acid sequence of the DPEase from I. fonsfrigidae strain SP3-1 (IfDPEase) has a low similarity to other ketose 3-epimerase members. Therefore, we speculated that the IfDPEase may represent a new function in the ketose 3-epimerase family.…”
Section: Introductionmentioning
confidence: 99%